Synthesis and preliminary ex vivo evaluation of the spasmolytic activity of 1,3-thiazolium- and 1,3,4-thiadiazolium-5-methylthio- and 5-thioacetate derivatives - Luis José A. S.; Aquino Thiago M. De; Lira Bruno F.; Filho Petrônio F. A.; Scotti Marcus T.; Scotti Luciana; Moura Ricardo O. De; Junior Francisco J. B. Mendonça (Acta Pharmaceutica)
Seven new compounds have been synthetized in satisfactory yields (51-78 %) through the treatment of mesoionic 1,3-thiazolium-5-thiolate (4a-d) and 1,3,4-thiadiazolium- 5-thiolate (10a,b) with chloroacetic acid or methyl iodide: 1,3,4-thiadiazolium-5-methylthio- (11) and 5-thioacetate (12). The structure of the title compounds was elucidated by elemental analysis, IR, 1H and 13C NMR spectroscopy. The newly synthesized compounds 5a, 6a, 11 and 12 were evaluated for their ex vivo spasmolytic potential on four isolated smooth muscles (rat aorta and uterus, guinea pig ileum and trachea) and compared with scopolamine. Some of the compounds exhibited potent spasmolytic activity equal to or stronger than scopolamine